2002
DOI: 10.1007/pl00007495
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the hepatic arterial and portal venous blood flows during pregnancy with Doppler ultrasonography

Abstract: The results demonstrated that the hepatic perfusion increased during third trimester compared to nonpregnant level. Because the hepatic arterial blood flow remained unchanged during pregnancy, major determinant of the increase in the hepatic perfusion was the portal venous return. The data suggest that the hepatic arterial and portal venous vascular territories have regulatory mechanisms that allow for independent changes during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 20 publications
1
57
0
Order By: Relevance
“…For a moderate extraction ratio drug, such as NFV, an increase in hepatic blood flow could increase its systemic clearance. Assuming that, as in humans (Zhang et al, 2001), NFV is eliminated primarily by metabolism, the reported 50% increase in hepatic blood flow in pregnant women (Nakai et al, 2002) would not completely explain the doubling of NFV systemic clearance observed in the pregnant macaque. Thus, we conclude that the increased systemic clearance of NFV must be due, at least in part, to increased hepatic metabolism of NFV (see below).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For a moderate extraction ratio drug, such as NFV, an increase in hepatic blood flow could increase its systemic clearance. Assuming that, as in humans (Zhang et al, 2001), NFV is eliminated primarily by metabolism, the reported 50% increase in hepatic blood flow in pregnant women (Nakai et al, 2002) would not completely explain the doubling of NFV systemic clearance observed in the pregnant macaque. Thus, we conclude that the increased systemic clearance of NFV must be due, at least in part, to increased hepatic metabolism of NFV (see below).…”
Section: Discussionmentioning
confidence: 94%
“…Based on the intra-arterial data, we first computed F h of NFV. To do so, we assumed that NFV is cleared solely by the liver, hepatic blood flow in the macaque is 3.1 liter/h/kg (Boxenbaum 1980) and, as in humans, is increased by 50% during pregnancy (Nakai et al, 2002). In addition, we used the observed NFV blood/ plasma partition ratio of 0.67.…”
Section: Discussionmentioning
confidence: 99%
“…Splanchnic blood flow and portal vein blood will naturally increase as well. There are reports showing increased portal vein blood flow in pregnancy [6]. In pregnant women, it is known that some hormones like relaxin (RLX) affect vascular smooth muscles to make dilation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-related changes in hepatic blood flow in baboons could thus affect the CL of BUP. Although we do not have any data regarding hepatic blood flow in baboon pregnancy, Nakai et al (2002) have reported a tendency for hepatic arterial blood flow to increase with gestation in healthy pregnant women, from 0.57 6 0.31 l/min (nonpregnant) to 0.58 6 0.13 l/min (first trimester), 0.70 6 0.41 l/min (second trimester), and 1.06 6 0.55 l/min (third trimester).…”
Section: Discussionmentioning
confidence: 99%